Recovery of carrier frequency offset and set information for LTE device-to-device communications - Yoon, Jooheum; Lee, Changgyu; Kim, Yun Hee (Journal of communications and networks, 2019)
Sidelink channels have been standardized in the longterm evolution (LTE) to support device-to-device communications for public safety, vehicular-to-everything services, and other features. The channels provide sidelink synchronization signals (SSSs) for synchronization among the user equipment (TIE), which obtain the timing, carrier frequency offset (CFO), and sidelink identity from a synchronization source TIE. This paper focuses on the recovery of a CFO and the sidelink identity set information by exploiting the two primary SSS (PSSS) symbols after the symbol timing is obtained. We propose the use of detection metrics for the quantized CFO and set information by estimating a multi-path fading channel subject to unknown delay times and residual CFO (RFO) errors. The proposed metrics have been shown to be implementable with low complexity by exploiting the properties of the PSSS sequence. The metrics were also analyzed in multi-path fading channels without RFO errors for a quick estimate regarding the performance and guidelines of the sequence design. The results indicate that the proposed detection metrics outperform the conventional metric under realistic scenarios with unknown delay times and RFO errors.